2016
DOI: 10.1097/mpg.0000000000001097
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Direct or Conjugated Bilirubin Measurements As a Potential Screen for Biliary Atresia

Abstract: Newborn DB or CB measurements may have a high sensitivity and specificity for BA. Specificity can be further improved by using 99% reference intervals and/or repeat testing. Our findings can serve as the foundation for larger prospective studies, to determine whether newborn DB or CB measurements can be an effective screening strategy for BA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 19 publications
3
45
0
Order By: Relevance
“…24 Harpavat et al reported that newborn DB measurements had a high sensitivity and specificity for the screening of BA. 11,12,20,[25][26][27] In our study, using DB of 30 μmol/L as a cutoff to predict BA, the sensitivity was 100%, but the specificity was 52%. The area under the ROC curve of DB, DB/TB, CB MS /TB MS , and CB MS for predicting BA was 0.98, 0.95, 0.73, and 0.57, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…24 Harpavat et al reported that newborn DB measurements had a high sensitivity and specificity for the screening of BA. 11,12,20,[25][26][27] In our study, using DB of 30 μmol/L as a cutoff to predict BA, the sensitivity was 100%, but the specificity was 52%. The area under the ROC curve of DB, DB/TB, CB MS /TB MS , and CB MS for predicting BA was 0.98, 0.95, 0.73, and 0.57, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Identification of cholestatic infants at this point at the latest should leave enough time for completion of a well-organized diagnostic protocol and timely performance of PE before the age of 2 months. General awareness of newborn cholestasis and the practice of routine measurement of serum conjugated bilirubin in all jaundiced newborns older than 2 weeks could be endorsed by active education [27][28][29]. Stool color card screening has improved timing of PE, clearance of jaundice and native liver survival in Taiwan and Japan, where BA incidence is considerably higher than in Europe [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…This review summarizes these various theories and focuses on recent studies of pathogenesis. The compelling finding of mild direct hyperbilirubinemia at birth in infants who eventually went on to have BA begs the question as to whether BA is initiated in-utero [16]. …”
Section: Theories Of Pathogenesismentioning
confidence: 99%